THE PRICE LEVEL RESEARCH PROJECT. - Graham, Willard J. (The Accounting Review, 1954)
This article discusses the background of the price level research project. The U.S. Committee on Accounting Concepts and Standards, in 1951, issued a very excellent statement of the problem of the changing price levels and suggested one approach to its solution. In its statement' the Committee poses three questions: First, is modification of the conventional accounting approach to net income determination to give explicit recognition to changes in the value of the dollar a desirable development? Secondly, if so, what methods are most appropriate for measuring variations in the value of the dollar and for giving effects to such variations in financial reports?and third if such modification is desirable, how is disclosure best to be accomplished? One of the proposed solution to the problem include that in the measurement of profit, depreciation of fixed assets should be based on the current replacement cost and not on the original or historical cost. The practical application of this principle is not insuperably difficult. Similarly, there have been proposed many answers to the questions above question and these have been discussed in the article.